Neotrombicula orycti Taufflieb 1960 - Stekolnikov, Alexandr A. (Zenodo, 2018)
Neotrombicula orycti Taufflieb, 1960 Neotrombicula roubaudi var. orycti Taufflieb, 1960a: 44, pl. 6a–d. Holotype No data. Distribution Morocco (Oued Cherrat). Hosts Dipodillus campestris , Lemniscomys barbarus , Oryctolagus cuniculus , Passeriformes gen. sp., Rattus rattus. Published as part of Stekolnikov, Alexandr A., 2018, Taxonomy and distribution of African chiggers (Acariformes, Trombiculidae), pp. 1-233 in European Journal of Taxonomy 395 on page 181, DOI:10.5852/ejt.2018.395, http://zenodo.org/record/3829724